Design and synthesis of new fused carbazole-imidazole derivatives as anti-diabetic agents: In vitro α-glucosidase inhibition, kinetic, and in silico studies. Issue 5 (1st March 2019) - Adib, Mehdi; Peytam, Fariba; Shourgeshty, Reihaneh; Mohammadi-Khanaposhtani, Maryam; Jahani, Mehdi; Imanparast, Somaye; Faramarzi, Mohammad Ali; Larijani, Bagher; Moghadamnia, Ali Akbar; Esfahani, Ensieh Nasli; Bandarian, Fatemeh; Mahdavi, Mohammad
Graphical abstract: A new series of fused carbazole–imidazoles6a–w as potential α-glucosidase inhibitors was synthesized by one-pot two-step sequence. All the synthesized compounds were more active than acarbose as standard drug (IC50 = 750.0 ± 1.5 µM) with IC50 values in the range of 74.0 ± 0.7–298.3 ± 0.9 µM. Abstract: Twenty three fused carbazole–imidazoles6a–w were designed, synthesized, and screened as new α-glucosidase inhibitors. All the synthesized fused carbazole-imidazoles6a-w were found to be more active than acarbose (IC50 = 750.0 ± 1.5 µM) against yeast α-glucosidase with IC50 values in the range of 74.0 ± 0.7–298.3 ± 0.9 µM. Kinetic study of the most potent compound6v demonstrated that this compound is a competitive inhibitor for α-glucosidase (Ki value = 75 µM). Furthermore, the in silico studies of the most potent compounds6v and6o confirmed that these compounds interacted with the key residues in the active site of α-glucosidase.